2011
DOI: 10.1159/000313962
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding Renal Fanconi Syndrome: Step by Step Advances through Experimental Models

Abstract: Renal Fanconi syndrome (FS) is a generalized dysfunction of proximal tubular epithelial cells leading to the urinary leak of essential metabolites like phosphate, uric acid, glucose, amino acids and low molecular weight proteins. From inherited forms involving mutations on apparently unrelated genes to acquired forms induced by drugs, heavy metals or monoclonal immunoglobulin (Ig) light chains (LC), heterogeneous causalities of FS have complicated the understanding of this pathology for a long time. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 91 publications
1
27
0
2
Order By: Relevance
“…[53][54][55][56][57] An animal model for this variant has shown that the primary structure of the light chains is directly responsible for the pathologic findings observed, and a transgenic model has been created where the disease has been reversed with experimental manipulations. 57,[59][60][61] An incomplete form of this condition has also been reported, 62 emphasizing once more the importance of the physicochemical characteristics of the light chains in producing pathologic processes. Light chains from most of these cases (j type) exhibit a specific amino acid substitution at position 30, which provides resistance to catabolism, [59][60][61] promoting the formation of cytoplasmic inclusions.…”
Section: Metabolism Of Light Chains In Proximal Tubules/handling Of Pmentioning
confidence: 98%
See 1 more Smart Citation
“…[53][54][55][56][57] An animal model for this variant has shown that the primary structure of the light chains is directly responsible for the pathologic findings observed, and a transgenic model has been created where the disease has been reversed with experimental manipulations. 57,[59][60][61] An incomplete form of this condition has also been reported, 62 emphasizing once more the importance of the physicochemical characteristics of the light chains in producing pathologic processes. Light chains from most of these cases (j type) exhibit a specific amino acid substitution at position 30, which provides resistance to catabolism, [59][60][61] promoting the formation of cytoplasmic inclusions.…”
Section: Metabolism Of Light Chains In Proximal Tubules/handling Of Pmentioning
confidence: 98%
“…57,[59][60][61] An incomplete form of this condition has also been reported, 62 emphasizing once more the importance of the physicochemical characteristics of the light chains in producing pathologic processes. Light chains from most of these cases (j type) exhibit a specific amino acid substitution at position 30, which provides resistance to catabolism, [59][60][61] promoting the formation of cytoplasmic inclusions.…”
Section: Metabolism Of Light Chains In Proximal Tubules/handling Of Pmentioning
confidence: 98%
“…8,9 Monoclonal gammopathy is a main cause of RFS in adults .50 years of age. 10 PT dysfunction and RFS may also result from congenital disorders, such as Dent disease and cystinosis, with defective receptor-mediated endocytosis as a common feature. [11][12][13] There is a remarkable heterogeneity in the capacity of free LCs to induce renal tubular damage.…”
mentioning
confidence: 99%
“…In proximal cells, the electrochemical gradient generated by the basolateral Na + -K + -ATPase facilitates the activity of sodium dependent co-transporters expressed at the apical side, allowing the reabsorption of glucose, phosphate, and others [1]. To maintain the electrochemical gradient, proximal cells have high metabolic rates and are rich in mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…They also have endocytic receptors such as megalin and cubilin that are critical for the reabsorption of filtered proteins [2]. Thus, the mechanism of FS can be categorized as the inhibition of (1) Na + -K + -ATPase activity [1], (2) mitochondrial activity, and (3) receptor-mediated endocytosis.…”
Section: Introductionmentioning
confidence: 99%